CORN HAIR EXTRACT AS CORROSION INHIBITOR FOR ST37 STEEL IN 3% HCL MEDIA - Sefrilita Risqi Adikaning Rani; Rahmaniah Rahmaniah; Hernawati Hernawati; Nurhidayah Nurhidayah; Fira Yurdanianti (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2023)
The research aims to analyze the impact of the concentration of the extracted corn hair inhibitor and the immersion time in reducing the formation of pitting corrosion with or without cracks of ST37 steel. The mass loss method and SEM analysis were applied used in this study to provide a reliable and accurate measurement of the inhibitor's effectiveness due to the corrosion formation. The results indicated that both concentrations of the inhibitor and the immersion time significantly impacted the morphological characteristics of the ST37 steel through the reduction of various types of corrosion. It indicated that the immersion time and the corrosion inhibitor concentration were related to the corrosion rate. The longer the sample was immersed, the greater the mass loss that occurred because the more Fe(OH)2 layers were formed. While the higher the concentration of inhibitor used, the lower the corrosion rate by hindering the diffusion of corrosion media to the surface of the sample. The results also indicated that the test of morphological characteristics of ST37 steel shows four types of corrosion formed such as stress, uniform, pitting, and pitting corrosions. Overall, this research demonstrates the potential use of corn hair extracted from waste material as an effective inhibitor for reducing the corrosion rate of ST37 steel. The findings of the research could have important implications in developing new sustainable corrosion inhibitors for the future manufacture of corn hair inhibitors in reducing the corrosion rate of ST37 steel.